Practice and Reflection on Inter-school Credits in College English Courses - Zhao, Mingfei (Transactions on Social Science, Education and Humanities Research, 2023)
Through the practice of teaching cross-school credit courses in college English classes, the innovative model of combining cross-school credit with flipped classroom is implemented. The practice has proved that the innovative teaching mode has promoted the improvement of students’ listening learning effect and learning ability, and has reached the expected teaching goal. At the same time, the teaching level and scientific research ability of teachers have been improved.